Effect of Bacterocin Produced by Enterococcus Faecium on Bacteria that Cause Diarrhea in Young Horses and a Goat - Jinan Mohamed Husan Faeroozali (Journal of Global Pharma Technology, 2018)
400 samples (200 samples from feases healthy young goats and infected with diarrhea and 200 samples from feases healthy and infected horses) were collected from the veterinary hospital and veterinary health centers in Najaf city for the period from January to April 2016. All isolates were subjected to cultural, microscopic and biochemical tests using Vitek2 for identification up to the species. The results showed that (43) isolates belong to Enterococcus faecium of which (30) isolates from diarrhea cases and (13) isolates from of healthy young, (32) isolates of which (22) isolates belonged to E.coli and (10) isolates belonged to Salmonella spp. All isolates were subjected to cultural, microscopic and biochemical tests by using strip (API-20E). The sensitivity of these isolates (32) was tested for antibiotics. Results revealed that isolates showed multi resistance to antibiotics. All isolates of E.coli and Salmonella spp. resistant to some antibiotics for Gram- negative Bacteria and belonging to the group Enterobacteriaceae. And detection of the ability of E. faecium local isolates to produce Bacteriocin by testing the inhibitory activity on agar and broth in two media MRS, BHI and two methods against bacteria cause diarrhea. And the isolates showed clear effect on the gram -negative bacteria causing diarrhea in young goats and young horses , by inhibitor zone between (13-20) mm and was MRS liquid and solid the best media from the brain heart infusion.Keywords: Enterococcus faecium bacteria, Bactriocin, inoculation steps GPID Card, sensitivity bactria for antibiotics, biochemical test, Detection methods for bactriocin